LFM Radar Convolution Jamming Suppression Based on Oblique Projection in FrFT Domain - Wang Jun; Ping Fulong; Zhao Yuan; Tang Bin (MATEC Web of Conferences, 2016)
Convolution false-targets jamming against LFM fire-control radars generates range and velocity false targets which are coherent with target echo, which increases the difficulty of jamming detection and suppression and makes the victim radar system lost the track of real target. To combat against this type of jamming, the uncorrelated characteristic between the jamming and echo in FRFT domain is discussed firstly. Thus, an oblique projection operator which is capable of suppress convolution false-targets jamming is built. The simulation results showed the operator have little effect on the echo and proved the effectiveness of this method.